Currículo de graduação em educação física: o desenho universal como princípio para a inclusão nas aulas de educação física - OLIVEIRA JÚNIOR, Luciano Cordeiro de (2020)
It is a study about the curriculum of twenty Physical Education courses, in the best institutions of higher education in Brazil, according to University Ranking Folha (2017). It aims to understand how these courses work inclusion in their curriculum; to analyze whether the concept of inclusion in the curriculum of the courses analyzed respects the principles of Universal Design for Learning; and propose ways that favor the establishment of inclusion in the curriculum of physical education, in accordance with the principles of universal design for learning. Regarding the methodology of the research, we adopted as a theoretical orientation the qualitative approach, and as a research strategy the bibliographic study, which allowed us to reflect on this phenomenon, from the menus of the courses of the mentioned courses, available on the website of the investigated institutions. To do this, we map the content of the subjects focused on the theme of inclusion and categorize how the inclusion is approached in such courses. We used the content analysis of Bardin (2011) for data processing; and field concepts in Bourdieu (1989, 1996, 2003 and 2014); Universal design in (CARLETTO; CAMBIAGHI, 2016); and (CAST, 2011) as a theoretical contribution. The results show that, even though the courses analyzed perceive the inclusion of accessibility, no discipline offered in the twenty Brazilian Physical Education courses in the universe of this research, develop the inclusion from the perspective of the Universal Design, focus only on the issue of physical disabilities, which ratifies the importance of a curricular restructuring in order to actually mainstream inclusion and not only in favor of students with disa